The Varying Effects of Family Relationships in Entrepreneurial Teams. (January 2013) - Brannon, David L.; Wiklund, Johan; Haynie, J. Michael
A majority of entrepreneurial teams contain family relations but little is known about the implications of such family relationships in the formative stages of new venture creation. We examine two distinct types of family relationships in these teams; romantic couples and biologically linked teams and how such relationships influence the probability of ever achieving first sales. Relying on social identity theory, and a longitudinal sample of 295 nascent teams, we find that these relationships matter in important ways. Our conceptualizations and results have implications for the entrepreneurial teams and family business literatures.